2019
DOI: 10.3126/kmcrj.v3i3.35686
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Brand Preference in Buying Car in Nepal

Abstract: The main objective this study is to identify the factors affecting the consumer brand preference in the choice of car in Kathmandu, Nepal. The study examines how the price perception, appearance perception and brand personality affect in the consumer brand preference in the buying of car in Nepalese market. The study focuses on how the consumer preferred to select the car and which factor has the more prominent role for brand preference and selection of car. Primary data has been used in the study. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Fathima (2019) studied consumers' brand preferences toward mobile phones and found that brand preference has been affected by the appearance, price, and attributes that influence the purchase decision of mobile phones but less than the social factor. Rai (2019) found that the price does not significantly impact the brand selection toward passenger cars. However, brand personality and appearance influence brand preference when buying passenger cars.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Fathima (2019) studied consumers' brand preferences toward mobile phones and found that brand preference has been affected by the appearance, price, and attributes that influence the purchase decision of mobile phones but less than the social factor. Rai (2019) found that the price does not significantly impact the brand selection toward passenger cars. However, brand personality and appearance influence brand preference when buying passenger cars.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Regarding the previous empirical evidence, there needs to be more consistency in the research findings on the brand preference issue. For example, Rai and Budhathoki (2023) found that product attributes significantly influence brand preference, but Rai (2019) found that product attributes do not considerably influence brand preference. Similarly, Fathima (2019) discovered that the product's prices significantly affect brand preference, but Laohakosol et al (2019) found that price does not influence brand preference.…”
Section: Introductionmentioning
confidence: 99%
“…Brand preference is an essential component in understanding consumer behavior (Punj and Hillyer, 2004;Rai, 2019;Sukant, 2021) which has been able to catch a great deal of attention of marketers (Ebrahim et al, 2016). Buyers respond to the brands in a different way, which may be caused by different factors including their preference and loyalty (Jalilvand et al, 2016).…”
Section: Introductionmentioning
confidence: 99%